Gas-phase Smiles Rearrangement of Sulfonylurea Herbicides in Electrospray Ionization Mass Spectrometry - 张佳 柴云峰 王伟 尚伟 潘远江 (Chinese journal of chemistry, 2012)
In the negative ion mode of electrospray ionization tandem mass spectrometry （ES1-MS/MS） of four sulfonyl- urea herbicides, Smiles rearrangements were observed in rimsulfuron and nicosulfuron. In the case of rimsulfuron, two competitive gas-phase Smiles rearrangements initiated by nitrogen anion and oxygen anion respectively were witnessed. The ion-neutral complex was proposed as the reactive intermediate in the course of this unimoleeular dissociation reaction of the oxygen attack Smiles rearrangement route. The density functional theory （DFT） was carried out to elucidate the mechanism as well as to show the possible transition states and the intermediates.